Açai supplementation (Euterpe oleracea Mart.) attenuates cardiac remodeling after myocardial infarction in rats through different mechanistic pathways - Figueiredo, Amanda Menezes [UNESP]; Cardoso, Ana Carolina [UNESP]; Buzati Pereira, Bruna Leticia [UNESP]; Candido Silva, Renata Aparecida [UNESP]; Goncalves Della Ripa, Andrea Freitas [UNESP]; Bachiega Pinelli, Tatiana Fernanda [UNESP]; Oliveira, Bruna Camargo [UNESP]; Murino Rafacho, Bruna Paola [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Azevedo, Paula Schmidt [UNESP]; Okoshi, Katashi [UNESP]; Henrique Fernandes, Ana Angelica [UNESP]; et al. (Public Library of Science (PLoS), 2022)
Myocardial infarction has a high mortality rate worldwide. Therefore, clinical intervention in cardiac remodeling after myocardial infarction is essential. Ac¸ai pulp is a natural product and has been considered a functional food because of its antioxidant/anti-inflammatory properties. The aim of the present study was to analyze the effect of ac¸ai pulp supplementation on cardiac remodeling after myocardial infarction in rats. After 7 days of surgery, male Wistar rats were assigned to six groups: sham animals fed standard chow (SA0, n = 14), fed standard chow with 2% ac¸ai pulp (SA2, n = 12) and fed standard chow with 5% ac¸ai pulp (SA5, n = 14), infarcted animals fed standard chow (IA0, n = 12), fed standard chow with 2% ac¸ai pulp (IA2, n = 12), and fed standard chow with 5% ac¸ai pulp (IA5, n = 12). After 3 months of supplementation, echocardiography and euthanasia were performed. Ac¸ai pulp supplementation, after myocardial infarction, improved energy metabolism, attenuated oxidative stress (lower concentration of malondialdehyde, P = 0.023; dose-dependent effect), modulated the inflammatory process (lower concentration of interleukin-10, P0.001; dose-dependent effect) and decreased the deposit of collagen (lower percentage of interstitial collagen fraction, P0.001; dose-dependent effect). In conclusion, ac¸ai pulp supplementation attenuated cardiac remodeling after myocardial infarction in rats. Also, different doses of ac¸ai pulp supplementation have dose-dependent effects on cardiac remodeling.